Novel Wavelength Converters Based On Cross-phase Modulation (XPM) And Four-Wave Mixing (FWM) In A Single Mode Fibre (SMF) And Brillouin Sideband Amplification - Lopez, Jude (2004)
Two types of wavelength converters based on Cross-Phase Modulation (XPM) and Four-Wave Mixing (FWM) in a single-mode fibre (SMF) and Brillouin Amplification are analyzed. A sinusoidal intensity modulated message signal causes the generation of a phase-modulated signal in a two-channel system through the effects of XPM.